Syarah Hadis tentang Berbakti kepada Kedua Orang Tua - Iffah Faizatun Nabila (Gunung Djati Conference Series, 2023)
This study aims to discuss birrul walidain or devoted to both parents. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith while the material object is the hadith narrated by Muslim No. 122 about filial piety to parents. The results and discussion of this study indicate that the hadith narrated by Muslim No. 122 of authentic quality that meet the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Muslim No. 122 is relevant for the spirit and self-motivation to always be devoted to parents and not hurt them in the slightest.